Web Applications and Web Services: A Comparative Study - Sarhan, Qusay I.; Gawdan, Idrees S. (Science Journal of University of Zakho, 2018)
Software components that rely on the Internet in order to be accessed and used cover many aspects of our daily activities including email checking, weather checking, purchase ordering, and Facebook logging. Nowadays, these components are considered one of the most valuable and fundamental rights in human’s life. However, accessing and using the functionality of such components are performed using two techniques: web applications or traditional web services. Determining which one of the techniques is better suited for delivering the functionality of an Internet-based software component is not an easy task to decide. Therefore, this paper aimed to make a comparative analysis and study of both techniques alongside many directions to help web developers make the right choice to deliver the functionality of Internet-based software components. This is achieved by providing them with a set of requirements that have been proposed by the authors. The proposed requirements clarify a number of misunderstandings and issues peculiar to both techniques. Furthermore, this paper has provided a comparative table of both techniques. To the best of our knowledge, so far there is no comprehensive comparative study has been conducted in this context which was the rationale for the authors to carry out this study.